The role of melatonin in cardioprotection : an investigation into the mechanisms involved in glucose homeostasis, microvascular endothelial function and mitochondrial function in normal and insulin resistant states - Nduhirabandi, Frederic (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)-- Stellenbosch University, 2014.